2013
DOI: 10.1016/j.neulet.2012.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic inferences modulate N400 during sentence comprehension: Evidence from picture–sentence verification

Abstract: The present study examines the online realization of pragmatic meaning using event-related potentials (ERPs). Participants read sentences including the English quantifier some, which has both a semantic meaning (at least one) and a pragmatic meaning (not all). Unlike previous ERP studies of this phenomenon, sentences in the current study were evaluated not in terms of their truth with respect to the real world, but in terms of their consistency with a picture presented before the sentence. Sentences (such as “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 15 publications
3
44
0
Order By: Relevance
“…Pragmatic processing indeed affected the N400. Moreover, we replicated findings of different participant groups based on behavioral responses (Hunt et al, ; Noveck & Posada, ; Politzer‐Ahles et al, ; Spychalska et al, ) and showed that ERPs differed between groups on late sentence positions. As a whole, the present pattern of results is explained well, though not perfectly, by our probabilistic pragmatic processing model.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Pragmatic processing indeed affected the N400. Moreover, we replicated findings of different participant groups based on behavioral responses (Hunt et al, ; Noveck & Posada, ; Politzer‐Ahles et al, ; Spychalska et al, ) and showed that ERPs differed between groups on late sentence positions. As a whole, the present pattern of results is explained well, though not perfectly, by our probabilistic pragmatic processing model.…”
Section: Discussionsupporting
confidence: 85%
“…In the present experiment, the N400 was accompanied by a late positivity. Similar effects have been interpreted as reflecting logical‐semantic revision (Spychalska et al, ) or disconfirmed expectations (Hunt et al, ). Recently, it has been suggested that positivities like the current one may be linked to the sentence–verification paradigm itself and reflect task‐related effects rather than semantic or pragmatic processing per se .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Such a pattern would indicate that processing measures at the rest in this sort of paradigm do not directly reflect scalar inference-making or meaning enrichment per se, but its downstream consequences (i.e., predictions of upcoming words based on a different interpretation of the scalar expression some). This has also been argued to be the case in event-related potential experiments that use brain responses to downstream words to make indirect inferences about the processing of some, rather than directly measuring the response to some itself (Hunt, Politzer-Ahles, Gibson, Minai, & Fiorentino, 2013;Nieuwland, Ditman, & Kuperberg, 2010;Noveck & Posada, 2003). It should be noted, however, that there was a significant interaction on regressions to the quantifier, such that there were more regressions to some in downward-entailing contexts than in upward-entailing contexts (see Tables 2 and 3); this may be consistent with the conjecture that seeing the rest causes participants to look back at the quantifier and re-evaluate its interpretation (perhaps by enriching the meaning with "not all").…”
Section: Discussionmentioning
confidence: 99%
“…The expected rate of incorrect answers predicts the dominance of the pragmatic interpretation: cca. 40% of logical compared to 60% of pragmatic answers (Hunt Politzer-Ahles, Gibson, Minai, and Fiorentino 2013;Noveck, 2001;Noveck and Posada 2003). Logical and pragmatic comprehension of sentences with the quantifier some was tested by giving different instructions to participants: one group were instructed to treat the quantifier some as some and possibly all and the other as some but not all (Bott and Noveck 2004;Noveck and Sperber 2007;Rips 1975).…”
Section: Methodsmentioning
confidence: 99%